Staggered Two-Bolt Connections in Transmission Towers: A Comprehensive Study on Failure Mechanisms and Design Codes - Songzhao Qu; Yang Zhou; Peng Yin; Xiongyan Li; Hairong Wu; Wenming Wang; Shuhao Huo; Wei An; Qiusong Tian; Yijin Wu (Buildings)
Steel-lattice transmission towers require efficient and reliable connection designs to ensure structural safety and cost-effectiveness. While traditional gusset plate connections increase their complexity and structural weight, direct bolted connections offer a simpler and lighter alternative. However, the adoption of staggered bolt arrangements, necessitated by the geometric constraints of chord angle members, challenges the applicability of existing design standards—particularly regarding block shear and net section failure modes. This study explores the structural behavior of staggered two-bolt angle connections through a combination of experimental testing and numerical modeling. Twelve full-scale specimens were subjected to axial tension to investigate the effects of key geometric parameters, including end distance, edge distance, and bolt stagger. Finite element analyses, which incorporate material nonlinearity and fracture criteria, delve deeper into the stress distribution and failure mechanisms. The results demonstrate significant deviations in failure modes compared with conventional parallel bolt arrangements, underscoring the limitations of current design standards (DL/T 5486, ASCE 10-15, and EN 1993-1-8) in accurately predicting the capacity of staggered connections. Based on the identified failure modes of staggered two-bolt connections, this study proposes an enhanced design methodology for member fracture capacity, incorporating block shear calculation models from the three aforementioned standards. Comparative analysis demonstrates that the ASCE standard provides superior predictive accuracy, with experimental validation exceeding 95% agreement. The study culminates in specific design recommendations for staggered two-bolt connections, offering critical insights into stress redistribution mechanisms, material behavior, and deformation-induced failure patterns. These findings contribute to the development of more accurate and safer design guidelines for bolted connections in steel transmission towers.